Mechanisms of institutional continuity in neoliberal "success stories": Developmental regimes in Chile and Estonia - Aldo Madariaga (Max Planck Institute for the Study of Societies, 2013)
How do neoliberal political economies threatened with declining competitiveness and social cohesion manage to remain neoliberal over time? This paper explores mechanisms of neoliberal continuity in Chile and Estonia by extending gradualist approaches to institutional change with the notion of institutional hierarchy. Neoliberal continuity, it is argued, depends on the ability of dominant groups to defend those institutions that are more favorable to their interests while altering those that are not in order to obtain political support from other social groups. The question is explored in relation to the parallel trajectory of two policy domains: monetary policy (exchange rates) and industrial policy. Dominant groups try to retain a conservative monetary policy and a neutral industrial policy by altering their parameters (marginal adjustment), narrowing their interpretation (solidification), or negotiating minor/larger concessions (accommodation/compromise). While these mechanisms have allowed dominant groups in Chile and Estonia to retain neoliberalism, the timing and combination of different mechanisms over time have generated different trajectories of continuity. Estonia remains closer to a neoliberal orthodoxy whereas Chile has a more pragmatic trajectory. – – Auf welche Weise gelingt es neoliberalen Ländern, deren Wettbewerbsfähigkeit und sozialer Zusammenhalt bedroht sind, neoliberal zu bleiben? Das Papier untersucht Mechanismen neoliberaler Kontinuität in Chile und Estland, indem es ein Modell institutioneller Hierarchien mit gradualistischen Ansätzen des institutionellen Wandels verbindet. Die neoliberale Kontinuität eines Landes, so das Argument, hängt davon ab, wie erfolgreich einflussreiche gesellschaftliche Gruppen Institutionen unterstützen, die ihren Interessen zuträglich sind, und jene umgestalten, bei denen das nicht so ist, damit sie politische Unterstützung von anderen gesellschaftlichen Gruppen erhalten. Die Frage wird im Verhältnis zu parallel verlaufenden Trajektorien zweier politischer Domänen untersucht: Geldpolitik (Wechselkurse) und Industriepolitik. Vier Mechanismen werden beschrieben, die von einflussreichen Gruppen genutzt werden, um konservative Geld- und neutrale Industriepolitik aufrechtzuerhalten: marginale Korrektur (Änderung der Parameter); Verfestigung (konkrete Deutung); Kulanz/Kompromiss (Einigung auf mehr oder weniger große Zugeständnisse). Anhand dieser Mechanismen konnte der Neoliberalismus in Chile und Estland gewahrt werden. Durch die zeitliche Abfolge der Ereignisse und die Kombination verschiedener Mechanismen sind unterschiedliche Kontinuitätstrajektorien entstanden. So bleibt Estland näher an einer neoliberalen Rechtgläubigkeit, während Chile sich auf einem pragmatischen Entwicklungspfad befindet.
Keywords: 300